Penyuluhan Pentingnya Pendidikan Untuk Perempuan Millenial - Nurdiyana Nurdiyana (Jurnal Loyalitas Sosial: Journal of Community Service in Humanities and Social Sciences, 2019)
Education can improve the standard of living for the better. The need for the importance of education does not only belong to men, women also have the same opportunity to study up to university level. But the reality is that not all women can go to college. Problems related to lack of interest and knowledge of the importance of education were found in Sasak Village, especially for the problem of education for young women there, most of whom only completed education only to the high school / equivalent level. To overcome this, activities need to be held to educate about the importance of education. The method used in this activity is expository, namely in the form of material delivery verbally and social approach, namely looking at the educational background of the community in delivering the material. The results obtained in this activity were that the community's insight increased more about the importance of education, because previously they assumed that women did not have to study until college. Knowledge gained by the community in this activity can motivate teenagers to be able to continue their education to college, and can change the views of parents about the importance of education. It is expected that counseling activities on the importance of education will be sustained supported by the participation of all citizens and the role of the Regional Government to be able to facilitate local people so that they can have the opportunity to continue their education to higher education.